2006
DOI: 10.1007/s11746-006-5045-7
|View full text |Cite
|
Sign up to set email alerts
|

Practical implications of the phase‐compositional assessment of lipid‐based food products by time‐domain NMR

Abstract: The objective of this work is to determine the solid fat content (SFC) of the fat-oil phase in oil-in-water (O/W) emulsions, i.e., the droplet SFC, using transverse relaxation decay deconvolution (TRDD) analysis. The TRDD NMR experiment classifies protein protons as mobile, semimobile, and nonmobile. Hence, protein contributes more or less to the solid content detected by TRDD as a function of pH, protein content, and protein denaturation. By taking into account the protein contribution to the overall solid co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…Solid fat crystals have relaxation times below 70 μs [30]. Also, for β and β′ fat crystal's T 2 relaxations are less than 45 μs and α crystals relax at 12 μs [31]. It is observed that at lower concentrations there is a significant (P N 0.05) decrease in the free induction relaxation times at 30°C when compared to 5°C (Fig.…”
Section: Mobility Of Protons In the Crystalline Network And The Liquimentioning
confidence: 85%
See 1 more Smart Citation
“…Solid fat crystals have relaxation times below 70 μs [30]. Also, for β and β′ fat crystal's T 2 relaxations are less than 45 μs and α crystals relax at 12 μs [31]. It is observed that at lower concentrations there is a significant (P N 0.05) decrease in the free induction relaxation times at 30°C when compared to 5°C (Fig.…”
Section: Mobility Of Protons In the Crystalline Network And The Liquimentioning
confidence: 85%
“…130 ms and 200 to 500 ms in the temperature range studied. Duval, van Duynhoven and Bot [31] reported that mobile oil has T 2 relaxations greater than 2 ms. Hence, the aforementioned relaxations are attributed to the oil phase.…”
Section: Mobility Of Protons In the Crystalline Network And The Liquimentioning
confidence: 98%
“…Following the work of Van Duynhoven et al [1], Trezza et al [2] recently, demonstrated that greater accuracy in the measurement of the solid fat content could be achieved from combined FID and CPMG acquisition and when the signal is analysed with semi-empirical mathematical functions for solid, semi-solid and liquid components. An extension of this method has also been proposed in order to adapt the method to nonanhydrous fat products such as emulsions [3]. Indeed, in emulsions the contribution of non-fat solid-like protons such as non-echangeable protein protons to the solid phase has to be taken into account.…”
Section: Solid and Liquid Fat Relaxationmentioning
confidence: 99%
“…Hence, the aforementioned relaxations are attributed to the oil phase. Duval, van Duynhoven, and Bot (2006) reported that mobile oil has T 2 relaxations greater than 2 ms. Given this, the relaxations in the range of 50-70 ms are attributed to the immobilized or entrained oil (less mobile oil) and those in the range of 200-500 ms to the mobile liquid oil.…”
Section: Resultsmentioning
confidence: 99%